1990
DOI: 10.1093/jac/25.suppl_a.1
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro activity of azithromycin, erythromycin, ciprofloxacin and norfloxacin against Neisseria gonorrhoeae, Haemophilus ducreyi, and Chlamydia trachomatis

Abstract: The minimum inhibitory concentrations (MICs) of azithromycin, erythromycin, ciprofloxacin and norfloxacin for 300 strains of Neisseria gonorrhoeae, 100 strains of Haemophilus ducreyi and six strains of Chlamydia trachomatis were determined. The two quinolones were more active against gonococcal strains than were the two macrolides. Azithromycin was approximately eight-fold more active against N. gonorrhoeae than was erythromycin (MIC90: 0.25 mg/l azithromycin, 2.0 mg/l erythromycin). The Mtr phenotype of gonoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
19
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(25 citation statements)
references
References 0 publications
6
19
0
Order By: Relevance
“…In vitro susceptibility testing has clearly indicated successful suppression of chlamydial growth by both drugs, as demonstrated by a MIC and MBC of 0.35 g/ml for ciprofloxacin and 0.5 g/ml for ofloxacin. These results are in good accord with those published by others (4,7,22,28,38,42,44,45,46,49). Treatment failures observed for ciprofloxacin, however, present an apparent contradiction to results of determination of MIC and MBC, whereas data of ofloxacin appeared to be consistent.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In vitro susceptibility testing has clearly indicated successful suppression of chlamydial growth by both drugs, as demonstrated by a MIC and MBC of 0.35 g/ml for ciprofloxacin and 0.5 g/ml for ofloxacin. These results are in good accord with those published by others (4,7,22,28,38,42,44,45,46,49). Treatment failures observed for ciprofloxacin, however, present an apparent contradiction to results of determination of MIC and MBC, whereas data of ofloxacin appeared to be consistent.…”
Section: Discussionsupporting
confidence: 91%
“…For C. trachomatis, such in vitro susceptibility testing indicated good activity for ciprofloxacin (22,38,45,46,49). However, in clinical trials a high rate of treatment failure has been observed with this drug.…”
mentioning
confidence: 99%
“…2A). These results suggest that the MIC of AZI for 90% of chlamydia grown in cultured HeLa cells is 100 ng/ml and that AZI is about threefold less active than ERY, a finding that agrees well with previous estimates of chlamydial sensitivity to AZI (14,17 Figure 2B demonstrates that de novo protein synthesis in chlamydia was not inhibited if the inoculating EBs had been exposed previously to AZI (lanes 1 and 2). In contrast, when chlamydia were treated with AZI for 15 min at 18 hpi (at which time they are predominantly intracellular RBs), complete inhibition of de novo protein synthesis was observed (lane 3).…”
Section: Concentration Of Azi That Inhibitssupporting
confidence: 89%
“…Tetracyclines have been used frequently for chlamydial infections for many years, although they have some undesirable side effects. Recently, some new quinolones have been reported to have antichlamydial activity in vitro (1,7,9,16), and some of them have successfully been applied to chlamydial infections in humans (2,3). Sparfloxacin has been reported to have potent antichlamydial activity (10), but its position in antichlamydial chemotherapy remains uncertain because of the relatively few comparative data available.…”
mentioning
confidence: 99%